The HABP2 G534E polymorphism does not increase nonmedullary thyroid cancer risk in Hispanics. Issue 3 (May 2016) - Bohórquez, Mabel E; Estrada, Ana P; Stultz, Jacob; Sahasrabudhe, Ruta; Williamson, John; Lott, Paul; Duque, Carlos S; Donado, Jorge; Mateus, Gilbert; Bolaños, Fernando; Vélez, Alejandro; Echeverry, Magdalena; et al.
Abstract : Familial nonmedullary thyroid cancer (NMTC) has not been clearly linked to causal germline variants, despite the large role that genetic factors play in risk. Recently, HABP2 G534E (rs7080536A) has been implicated as a causal variant in NMTC. We have previously shown that the HABP2 G534E variant is not associated with TC risk in patients from the British Isles. Hispanics are the largest and the youngest minority in the United States and NMTC is now the second most common malignancy in women from this population. In order to determine if the HABP2 G534E variant played a role in NMTC risk among Hispanic populations, we analyzed 281 cases and 1105 population-matched controls from a multicenter study in Colombia, evaluating the association through logistic regression. We found that the HABP2 G534E variant was not significantly associated with NMTC risk ( P =0.843) in this Hispanic group. We also stratified available clinical data by multiple available clinicopathological variables and further analyzed the effect of HABP2 on NMTC presentation. However, we failed to detect associations between HABP2 G534E and NMTC risk, regardless of disease presentation ( P ≥0.273 for all cases). Therefore, without any significant associations between the HABP2 G534E variant and NMTC risk, we conclude that the variant is not causal of NMTC in this Hispanic population.